Myxosporidiosis (Myxozoan Infections) in Warmwater Fish - Justin Stilwell; Roy P.E. Yanong (EDIS)
Discusses myxozoans--metazoan parasites of marine and freshwater invertebrates and fishes. Provides examples of species that infect aquarium and warmwater species; morphology; general life cycle and transmission; methods for diagnosing infections in fish; and advice for treatment, prevention, and control.